Caffeoylquinic acids from aronia juice inhibit both dipeptidyl peptidase IV and α-glucosidase activities. (July 2020) - Imai, Momoko; Yamane, Takuya; Kozuka, Miyuki; Takenaka, Shigeo; Sakamoto, Tatsuji; Ishida, Tetsuo; Nakagaki, Takenori; Nakano, Yoshihisa; Inui, Hiroshi
Abstract: Aronia ( Aronia melanocarpa ) contains many polyphenols including cyanidin-3, 5-diglucoside, and these polyphenols have beneficial effects on lifestyle-related diseases such as type 2 diabetes and obesity. In type 2 diabetes and obesity model KKA y mice, drinking water supplemented with aronia juice reduced blood glucose levels partly through inhibition of dipeptidyl peptidase IV (DPP IV) activity by cyanidin-3, 5-diglucoside. The objective of this study was to find α-glucosidase inhibitors in aronia juice. Polyphenols in aronia juice were first separated using flash chromatography on a reversed-phase column. The fraction with inhibitory activity was further separated using reversed-phase HPLC. Two peak fractions showed inhibitory activity. LC-MS/MS analysis of the fractions indicated that they contained 3-caffeoylquinic acid (3-CQA) and 4-caffeoylquinic acid (4-CQA), respectively. Both CQAs also inhibited DPP IV activity. The results suggest that caffeoylquinic acids in aronia juice are important for the amelioration of type 2 diabetes by the juice. Highlights: Two α-glucosidase inhibitors were purified from aronia juice. These inhibitors were identified to be 3- and 4-caffeoylquinic acids. Both 3- and 4-caffeoylquinic acids strongly inhibited dipeptidyl peptidase IV.